2017
DOI: 10.1016/j.ijscr.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

The first case report of failed single-anastomosis-duodeno-ileal bypass converted to One anastomosis gastric bypass/Mini-gastric bypass

Abstract: HighlightsRevisional bariatric surgery will rise in the future.The established single-anastomosis-duodeno-ileal bypass with sleeve gastrectomy (SADI-S) as the restrictive part of the procedure. Due to preserved pylorus, SG has the disadvantage of a high-pressure system with de-novo or worsening of existing gastroesophageal reflux disease in the long-term.One anastomosis gastric bypass/Mini-gastric bypass (OAGB/MGB) reduces the high-pressure system of SG in a low-pressure system of OAGB/MGB.OAGB/MGB might be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Numerous studies have described malabsorption as the predominant complication following SADI-S and DS interventions, resulting in consequential malnutrition, with prevalence rates ranging from 2% to 18.5% [ 117 , 118 , 119 ]. However, recent studies have identified GERD as a post-procedural side effect following SADI-S and DS [ 120 , 121 , 122 , 123 , 124 ].…”
Section: Surgical Choicementioning
confidence: 99%
“…Numerous studies have described malabsorption as the predominant complication following SADI-S and DS interventions, resulting in consequential malnutrition, with prevalence rates ranging from 2% to 18.5% [ 117 , 118 , 119 ]. However, recent studies have identified GERD as a post-procedural side effect following SADI-S and DS [ 120 , 121 , 122 , 123 , 124 ].…”
Section: Surgical Choicementioning
confidence: 99%
“…149,150 In addition, a case report about the failure of anastomosis gastric bypass/mini-gastric bypass rescuing in patients with GERD who underwent single-anastomosis -duodeno-ileal bypass has been published. 151 GERD after multiple bariatric surgeries might be caused by the repeated dissection of the angle of His and diaphragmatic crura and enlargement of natural orifices, such as the hiatal orifice. 152 Patients who underwent multiple bariatric surgeries are not a minority, and multiple operations have made their situations complicated.…”
Section: Multiple Revisional Surgeriesmentioning
confidence: 99%